Про одну статичну модель прогнозу голосування - Belyaeva, E. N.; Panin, V. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A simplified model of finances distribution among regions by some competing pre-election unions in the fight for the maximal number of votes is formulated. The model is reduced to the search of the equilibrium point by Nash. To determine the point a numerical method solving for monotone variational inequalities with a degenerate operator is used.